Transformation of Fatty Acids Catalyzed by Cytochrome P450 Monooxygenase Enzymes of Candida tropicalis - Eschenfeldt, William H. (American Society for Microbiology, 2003)
Candida tropicalis ATCC 20336 can grow on fatty acids or alkanes as its sole source of carbon and energy, but strains blocked in β-oxidation convert these substrates to long-chain α,ω-dicarboxylic acids (diacids), compounds of potential commercial value (Picataggio et al., Biotechnology 10:894-898, 1992). The initial step in the formation of these diacids, which is thought to be rate limiting, is ω-hydroxylation by a cytochrome P450 (CYP) monooxygenase. C. tropicalis ATCC 20336 contains a family of CYP genes, and when ATCC 20336 or its derivatives are exposed to oleic acid (C(18:1)), two cytochrome P450s, CYP52A13 and CYP52A17, are consistently strongly induced (Craft et al., this issue). To determine the relative activity of each of these enzymes and their contribution to diacid formation, both cytochrome P450s were expressed separately in insect cells in conjunction with the C. tropicalis cytochrome P450 reductase (NCP). Microsomes prepared from these cells were analyzed for their ability to oxidize fatty acids. CYP52A13 preferentially oxidized oleic acid and other unsaturated acids to ω-hydroxy acids. CYP52A17 also oxidized oleic acid efficiently but converted shorter, saturated fatty acids such as myristic acid (C(14:0)) much more effectively. Both enzymes, in particular CYP52A17, also oxidized ω-hydroxy fatty acids, ultimately generating the α,ω-diacid. Consideration of these different specificities and selectivities will help determine which enzymes to amplify in strains blocked for β-oxidation to enhance the production of dicarboxylic acids. The activity spectrum also identified other potential oxidation targets for commercial development.